2022
DOI: 10.3389/fonc.2022.845334
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration and Validation of a Nomogram Based on Axillary Ultrasound and Tumor Clinicopathological Features to Predict Axillary Lymph Node Metastasis in Patients With Breast Cancer

Abstract: BackgroundThis study aimed at constructing a nomogram to predict axillary lymph node metastasis (ALNM) based on axillary ultrasound and tumor clinicopathological features.MethodsA retrospective analysis of 281 patients with pathologically confirmed breast cancer was performed between January 2015 and March 2018. All patients were randomly divided into a training cohort (n = 197) and a validation cohort (n = 84). Univariate and multivariable logistic regression analyses were performed to identify the clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
15
1
Order By: Relevance
“…Finally, we constructed a nomogram to effectively predict survival probability for BC via integrating independent prognostic factors. Although age, TNM stage, and pathologic stage, ER status and PR status were considered as potential prognostic factors of BC [33,34]; however, we found that only four characteristics were the independent prognostic factors. Herein, the OCRL expression-based nomogram as a pretty survival predictive model was constructed to visually and directly show the risk scores of prognostic variables to 1-year, 5-year, 10-year survival, and further guided the clinical treatment and prevention of BC.…”
Section: Discussioncontrasting
confidence: 59%
“…Finally, we constructed a nomogram to effectively predict survival probability for BC via integrating independent prognostic factors. Although age, TNM stage, and pathologic stage, ER status and PR status were considered as potential prognostic factors of BC [33,34]; however, we found that only four characteristics were the independent prognostic factors. Herein, the OCRL expression-based nomogram as a pretty survival predictive model was constructed to visually and directly show the risk scores of prognostic variables to 1-year, 5-year, 10-year survival, and further guided the clinical treatment and prevention of BC.…”
Section: Discussioncontrasting
confidence: 59%
“… 25 , 26 For patients with BC, ultrasound is a conventional imaging method to evaluate lesions and ALN status, as it has low cost and no radiation. 27 In comparison, our study also focused on the combination of preoperative clinicopathological features and DLR methods to supplement more clinical feature information besides ultrasound images. This method can improve the performance and achieve the constraining effect of DLR features to make the model more robust.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have investigated the discriminatory performance of nomograms for predicting N status using retrospective clinicopathological data alone or in combination with imaging features [6,[8][9][10][11][12][13][14][15][16][17]. We aimed to externally validate and further develop a diagnostic tool for the noninvasive staging of N status using only routinely available clinicopathological data to improve the clinical utility of the model.…”
Section: Comparison With Prior Studiesmentioning
confidence: 99%
“…Multiple recent studies have presented prediction models for noninvasive staging of axillary nodal (N) status with the long-term aim of replacing SLNB for subgroups of patients with breast cancer [5][6][7][8][9][10][11][12][13][14][15][16][17]. Only routinely and preoperatively available data should be used for a feasible noninvasive diagnosis of axillary N status aimed at clinical implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation